The Folklore of Deinstitutionalization: Popular Film and the Death of the Asylum, 1973–1979 - Rondinone, Troy (Journal of American Studies, 2019)
The demise of America's state mental hospital system, or “deinstitutionalization,” has received much attention from sociologists and historians of medicine. Less understood is the manner in which the public experienced and came to terms with it. Using elements of folklore and horror studies, I will examine how popular films accommodated audiences to institutional decline and confirmed popular antistatist pessimism. The Exorcist (1973), One Flew over the Cuckoo's Nest (1975), Halloween (1978), and When a Stranger Calls (1979) helped weave a tapestry of distrust. By endorsing popular conceptions of institutional failure and presenting mythical narratives of individualist triumph, these films helped pave a path towards the conservative Reagan era to come.
1 citations (Crossref) [2023-10-31]
Keywords: dept.his; peer-reviewed